Application of geographic information systems in planning forest and land rehabilitation activities in Sukabumi Region III forestry service branch - Fergina Anggun; Fatimatuzahra Dinda Tsania; Sembiring Falentino; Parwati Lusiana Sani; Jakfar Any Elvia (BIO Web of Conferences)
The application of Geographic Information Systems (GIS) has become important in various fields, including the forestry sector which is experiencing rapid progress. The Sukabumi Region III Forest Service Branch uses GIS to monitor the distribution of critical land, a significant issue in forestry discussions. GIS allows the visualization of spatial data in thematic maps, making it easier to understand geographical conditions and the problems faced. This report discusses the application of GIS in forest and land rehabilitation planning in Sukabumi, focusing on analyzing the distribution of critical land and preparing rehabilitation planning maps.